Entrenching CALL for English Language Multicultural Pedagogy in Nigerian Secondary Schools: Issues, Prospects and Perceptions of Critical Stakeholders in Osun State, Nigeria - Mohammed Ademilokun; Anthony Adejuwon; Lara Olarewaju (CV. Rustam, 2024)
This paper examines the possibility of adoption of computer-assisted language learning (CALL) in Nigerian secondary schools especially those in Osun State, Nigeria in the light of recent developments necessitating greater familiarity with the computer by the students for their external examinations. The paper argues that secondary school students are more positioned now than ever to harness the benefits of CALL in developing necessary competences to excel in their English language exams and generally develop adequate proficiency in the language for their growth in the Nigerian nation and beyond. Data for the study comprise responses to questionnaires designed for secondary school students, English language teachers and Ministry of Education senior officials in Osun State Nigeria. The sample comprised 120 teachers across the three senatorial districts in Osun State, 36 teachers and 15 Ministry of Education officials. Data analysis revealed that there is great awareness of CALL among all the categories of subjects. In addition, the subjects emphasise the potential agency of CALL for enhancing the delivery of English language topics and the professional development of teachers, even though about 30 percent of the teachers sampled doubted its feasibility. The study therefore concludes that given the positive disposition of students to the introduction of CALL for English language teaching and being primary actors in the education process, there is need for immediate full-fledged adoption for English language teaching in Nigerian secondary schools.